2009
DOI: 10.1080/10903120802474513
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Portable Ultrasonography to Diagnose Fractures in an Austere Environment

Abstract: Our data show that use of ultrasound by an experienced clinician in the austere environment can be performed accurately and can possibly prevent unnecessary evacuations for suspected fractures requiring radiographic verification. The purpose of our study was to assess the accuracy of ultrasound examination in the austere, combat environment for diagnosis of orthopedic fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…It can also provide real-time guidance during fracture reduction and is more portable and less cumbersome for this purpose than traditional fluoroscopy (Chen et al, 2007;McManus et al, 2008;Patel et al, 2009). The portability of ultrasound has been underscored in a recent study that demonstrated its clinical usefulness in the diagnosis of fractures in more austere combat environments (McNeil et al, 2009). The role of sonography in the evaluation of the injured patient is ever evolving.…”
Section: Discussionmentioning
confidence: 97%
“…It can also provide real-time guidance during fracture reduction and is more portable and less cumbersome for this purpose than traditional fluoroscopy (Chen et al, 2007;McManus et al, 2008;Patel et al, 2009). The portability of ultrasound has been underscored in a recent study that demonstrated its clinical usefulness in the diagnosis of fractures in more austere combat environments (McNeil et al, 2009). The role of sonography in the evaluation of the injured patient is ever evolving.…”
Section: Discussionmentioning
confidence: 97%
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…7,8, Two studies used a second reference standard for some of the patients, either computed tomography when the plain radiographs were not definitive or a daily clinical evaluation for 72 hours with delayed imaging or return to full duty for military personnel. 34,42 Both the medical background and PoCUS training of the operators varied greatly across studies. Sixteen studies (53.3%) had emergency physicians performing and interpreting PoCUS examinations, four studies (13.3%) had surgeons (pediatric, hand, and/or orthopedic), five studies (16.7%) had radiologists or ultrasound fellows or technicians, and four studies (13.3%) included medical students or residents.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedside US also provides clinically useful information in settings outside of the traditional hospital, including military combat zones, 18 disaster areas, 19 and developing countries. 20 Although not traditional medical settings, it is important to have knowledge of how to use bedside US to assist in decision-making, such as evacuation protocols or prioritization of treatment.…”
mentioning
confidence: 99%